209k views
4 votes
4x-1=6x+3 Solve Multi-Step Equations

2 Answers

1 vote

Answer:

The answer is -2.

Step-by-step explanation:

4x−1=6x+3

Subtract 6x from both sides.

4x−1−6x=3

Combine 4x and −6x to get −2x.

−2x−1=3

Add 1 to both sides.

−2x=3+1

Add 3 and 1 to get 4.

−2x=4

Divide both sides by −2.

x= 4/-2

Divide 4 by −2 to get −2.

x=−2

User TheAnh
by
6.0k points
2 votes

Answer:

x = -2

Step-by-step explanation:

4x - 1 = 6x + 3

4x - 1 - 6x = 3

4x - 6x = 3 + 1

-2x = 4

x = 4 / -2

x = -2

User Squeazer
by
6.6k points